The Impact of Work Environment, Work Ethics, and Reward on Increasing Employee Productivity with Work Discipline as Intervening Variable - Wahidah, Zahrotul; Sumartik, Sumartik; Andriani, Dewi (Image : Jurnal Riset Manajemen, 2024)
This research aims to examine how the Work Environment, Work Ethic and Rewards affect the Increase in Employee Productivity of Tas Grosir Sederhana MSMEs with Work Discipline as an intervening variable. With quantitative methods and data analysis approaches using SmartPLS software and data collection techniques using Likert scale model questionnaires distributed to a sample of a number of populations (total sampling) of Tas Grosir Sederhana MSMEs, this study provides results that 1) Work Environment, Work Ethic and Reward variables do not have a significant effect on Employee Work Productivity 2) Work Environment, Work Ethic and Reward variables do not have a significant effect on Work Discipline 3) Work Environment Discipline variables affect Employee Productivity 4) Work Discipline variables are unable to mediate Work Environment, Work Ethic and Respect towards Employee Productivity. From the results of this study, the company should review its strategies and policies. This means that there are other factors of productivity that have more influence. This can be used as insight for companies in considering factors that can increase employee productivity.